WEB APPLICATION FRONT END QUALITY MODEL - A. V. Rezvanov; V. V. Bakhtizin (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The research results of modern quality models and the development of a new front end quality model have been reported. New metrics have been proposed for quality characteristics such as functionality, compatibility, usability, reliability and maintainability, which are essential for quality estimation of web application front end.